2017
DOI: 10.4103/pm.pm_87_17
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flavonoids on mechanism of modulation of insulin secretion

Abstract: Background:The development of alternatives for insulin secretion control in vivo or in vitro represents an important aspect to be investigated. In this direction, natural products have been progressively explored with this aim. In particular, flavonoids are potential candidates to act as insulin secretagogue.Objective:To study the influence of flavonoid on overall modulation mechanisms of insulin secretion.Methods:The research was conducted in the following databases and platforms: PubMed, Scopus, ISI Web of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 125 publications
(118 reference statements)
0
11
0
1
Order By: Relevance
“…It can be proposed that quercetin and kaempferol content of walnut leaf extract, act as an antioxidant and scavenger of free radicals, and have a role in beta cell regeneration and protects pancreatic islets. Their possible mechanisms can be associated with anti-diabetic effect, antioxidant effect (Alkhalidy et al, 2015;Kawser Hossain et al, 2016), impact on hepatic glucokinase (Vessal et al, 2003), inhibition of gastrointestinal absorption of glucose (Kwon et al, 2007), glucosuric effect (Beekmann et al, 2015), and/ or insulin-like external pancreatic mechanisms (Alkhalidy et al, 2015;Soares, Pereira Leal, Silva, Almeida, & Oliveira, 2017). In our study, concentrations of lipid profiles including TC, TG, and LDL-c were significantly higher in diabetic rats compared to the control group.…”
Section: Discussionmentioning
confidence: 44%
“…It can be proposed that quercetin and kaempferol content of walnut leaf extract, act as an antioxidant and scavenger of free radicals, and have a role in beta cell regeneration and protects pancreatic islets. Their possible mechanisms can be associated with anti-diabetic effect, antioxidant effect (Alkhalidy et al, 2015;Kawser Hossain et al, 2016), impact on hepatic glucokinase (Vessal et al, 2003), inhibition of gastrointestinal absorption of glucose (Kwon et al, 2007), glucosuric effect (Beekmann et al, 2015), and/ or insulin-like external pancreatic mechanisms (Alkhalidy et al, 2015;Soares, Pereira Leal, Silva, Almeida, & Oliveira, 2017). In our study, concentrations of lipid profiles including TC, TG, and LDL-c were significantly higher in diabetic rats compared to the control group.…”
Section: Discussionmentioning
confidence: 44%
“…Compounds 2 – 5 have the chalcone skeleton, which is an α-β-unsaturated ketone with two phenyl rings. There have been several reviews on the biological and pharmacological activities of chancones, including anti-cancer, anti-malarial, anti-microbial, anti-inflammatory, anti-protozoal and anti-HIV activities [ 33 ], as well as its role in diabetes control [ 15 , 34 , 35 ]. In a comprehensive study into modulating the therapeutic targets PPAR-γ, DPP-IV, α-glucosidase, PTP1B, ALR and insulin secretion via anti-diabetic chalcones and their structure–activity relationships [ 15 ], in particular, it was reported that the chalcone structure of which the carbonyl group was replaced with an oxime function exhibited enhanced DPP-IV inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…In a comprehensive study into modulating the therapeutic targets PPAR-γ, DPP-IV, α-glucosidase, PTP1B, ALR and insulin secretion via anti-diabetic chalcones and their structure–activity relationships [ 15 ], in particular, it was reported that the chalcone structure of which the carbonyl group was replaced with an oxime function exhibited enhanced DPP-IV inhibitory activity. In addition, there have been reports that nitrochalcones and prenylated chalcones increase insulin secretion and glucose uptake, respectively [ 34 ]. Among chalcones isolated in this study, 3 – 5 showed less inhibitory activity than 2 , indicating that chalcones substituted with additional methoxy group and/or sugar are less effective.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous studies reported that besides protecting pancreatic βcells from damage by oxidative stress, it also triggers the proliferation of β-cells within pancreatic islet (Pinent et al, 2008). Flavonoids play a role in controlling blood glucose by increasing insulin secretion through elevating metabolism of Ca 2+ and regenerate pancreatic β-cells (Dias Soares, Pereira Leal, Silva, Almeida, & de Oliveira, 2017;Ghorbani, Rashidi, & Shafiee-Nick, 2019). Through interaction with the ATP-sensitive K channels in the membrane of beta cells causing membrane depolarization and this situation will open Sodium gate channels.…”
Section: Resultsmentioning
confidence: 99%